Integral assessment of the spring water quality with the use of fuzzy logic toolkit - Repeta, Vyacheslav; Krykhovets, Oleksandra; Kukura, Yurii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
Water, as an important strategic resource, ensures the livelihood of people and the economic development of society. The effective use of water resources is one of the main goals of sustainable development. The possibility of using a particular water body depends on the degree of water pollution. The drinking water quality is characterized by the content of a significant number of chemical elements, while not only instrumental and analytical methods are used to determine certain criteria, but also methods in which parameters are assessed by experts, in particular organoleptic indicators. Accordingly, considering the use of the survey for expert assessment, the integral indicator of the drinking spring water quality is determined using the fuzzy logic toolkit. For the integral assessment of the drinking water quality, indicators are divided into three groups: organoleptic indicators of the water quality, general physical and chemical indicators of the water quality and quality indicators of the content of inorganic chemical elements. A universal set and corresponding terms are determined for the factors of each group as linguistic variables. For each linguistic variable, fuzzy sets are determined, a knowledge base is formed, and fuzzy logic equations are constructed. The results of the work are checked with the help of the Matlab Fuzzy Logic Toolbox package by obtaining the corresponding models. The models developed by the fuzzy logic toolkit will make it possible to assess the possibility of using drinking water sources and make informed decisions when using them for industrial and domestic needs.